Nomogram for predicting oral feeding intolerance in patients with acute pancreatitis - Bevan, Melody G.; Asrani, Varsha M.; Pendharkar, Sayali A.; Goodger, Rachel L.; Windsor, John A.; Petrov, Maxim S. (Nutrition (Burbank, Los Angeles County, Calif.), 2017)
Oral feeding intolerance (OFI) is a common complication of acute pancreatitis that leads to prolonged hospitalization, increased use of hospital resources, and impaired quality of life. However, there are no clinically useful predictors of OFI. The aims of this study were to determine whether gastrointestinal dysmotility is associated with the development of OFI, and whether the gastroparesis cardinal symptom index (GCSI) can be used as a predictive tool in a clinical setting. This was a prospective cohort study. The primary outcome was the development of OFI. Daily GCSI total score and subscores (nausea/vomiting, early satiety, and bloating) were recorded. Univariate and multivariate binary logistic regression analyses were conducted, adjusting for age, etiology of pancreatitis, severity, diabetes status, and time from symptom onset to hospital admission. The study included 217 consecutive adult patients with acute pancreatitis. Multivariate analyses showed significant associations between OFI occurrence and the total GCSI score on day 2 of hospital admission (odds ratio [OR], 1.42; 95% confidence interval [CI], 1.02–2.00), the highest total GCSI score (OR, 1.38; 95% CI, 1.03–1.86), the day 2 nausea/vomiting subscore (OR, 1.40; 95% CI, 1.04–1.89), the day 2 bloating subscore (OR, 1.25; 95% CI, 1.01–1.54), and the highest bloating subscore (OR, 1.32; 95% CI, 1.08–1.63). Gastrointestinal dysmotility is associated with the development of OFI and the GCSI has potential as a clinically useful predictive tool in the setting of acute pancreatitis. The developed nomogram holds promise but needs to be validated externally. •Gastrointestinal dysmotility is associated with oral feeding intolerance in acute pancreatitis.•The gastroparesis cardinal symptom index is a potentially useful tool to predict risk for oral feeding intolerance.•A predictive nomogram for risk for oral feeding intolerance has been developed.